2012
DOI: 10.7150/jca.4090
|View full text |Cite
|
Sign up to set email alerts
|

HER2 as a Prognostic Marker in Gastric Cancer - A Systematic Analysis of Data from the Literature

Abstract: Through the recent conduct of the ToGA trial, HER2 has shown to be predictive for the treatment with trastuzumab in advanced gastric and gastro-oesophageal cancer. When it comes to the prognostic properties the situation is different. Despite the fact that it is more than 20 years ago since the first studies demonstrating an association between a positive HER2 status and poor prognosis were published the issue is still controversial. In this current systematic review a large number of studies on HER2 and gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
144
4
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(164 citation statements)
references
References 43 publications
9
144
4
7
Order By: Relevance
“…Ulus Cerrahi Derg 2015; 31: 207-13 the intestinal type gastric cancer, 2-7% in diffuse-type gastric cancer, and 5-20% in the mixed type (6,8). In this study, HER-2 positivity was found in 9 patients (12%) with intestinal type gastric cancer (n=67).…”
mentioning
confidence: 70%
“…Ulus Cerrahi Derg 2015; 31: 207-13 the intestinal type gastric cancer, 2-7% in diffuse-type gastric cancer, and 5-20% in the mixed type (6,8). In this study, HER-2 positivity was found in 9 patients (12%) with intestinal type gastric cancer (n=67).…”
mentioning
confidence: 70%
“…Hoffman et al 36 proved that these FISH criteria for gastric cancer showed a higher concordance (93%) between HER2 amplification and overexpression in gastric cancer. Ruschoff et al 38, 45 (2010, 2012) Recently, Jorgensen and Hersom [56] (2012) reviewed previous studies with more than 100 patients and analysis of association between the HER2 status and survival or relevant clinicopathological characteristics. Forty-two publications with a total of 12,749 patients fulfilled the two criteria and were reviewed in detail.…”
Section: Gastricmentioning
confidence: 99%
“…HER2 over-expression occurs in up to 30% of all breast cancers [3] and at a similar rate in gastric cancers [4]. Over-expression is associated with decreased time to recurrence and poorer prognosis in breast cancer [3,5], and may be linked to worse prognosis and increased recurrence in gastric cancer [4,6].…”
Section: Introductionmentioning
confidence: 99%